Sentiment analysis using R: an approach to correlate bitcoin price fluctuations with change in user sentiments - Rahman, Shaomi; Hemel, Jonayed Nafis; Anta, Syed Junayed Ahmed; Al Muhee, Hossain (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.